Aspects of Islamic Civilization : As Depicted in the Original Texts - Arberry, A. J. (Lahore Suhail Academy, 2001)
The present volume is not intended as a competitor with Brockelmann and Hitti, Gibb and von Grunebaum, Rosenthal and Lewis, Levi-Provençal and Spuler and Gabrieli-to name but a few of the brilliant historians whose writings have done so much to recover and reinterpret the record. Its scope is at once more modest and, in a certain way, more fundamental. This book is a series of documents illustrating the development of Islamic civilization, texts translated from the languages in which they were originally composed by famous protagonists of that culture. The intention is to present a panorama of Muslim life and thought and achievement as depicted from within. The translations, a considerable part of which has not been published hitherto, are all the work of a single scholar and represent the gleanings of more than thirty years of assiduous reading. They are meant to throw light on the literary, intellectual and religious movements within Islam, as well as illuminating something of the politics and the sociology, ranging from the origins in the sixth century down to the present day. It should of course be confessed that they constitute the merest fragments of literatures preserved in overwhelming abundance, exceeding many times what has survived from ancient Greece and Rome, a repertory of many tens of thousands of volumes, the majority still in manuscript, not a few of immense length. The passages chosen, however, have been taken from the most highly esteemed and authoritative works; and the attempt has been made to construct a balanced and rounded picture.
Include Bibliography and Index.
Keywords: Islamic civilization -- Islamic literature -- Authoritarianism -- Arabic literature